Pengaruh Kemandirian Belajar dan Persepsi Siswa Tentang Metode Mengajar Guru Terhadap Hasil Belajar Siswa Kelas X Pada Mata Pelajaran Administrasi Umum di SMK Negeri 1 Padang Panjang - Zikra Aulia; Armiati Armiati (Universitas Negeri Padang, 2019)
This research is conducted to find out: (1) the influence of learning independence on student outcome, (2) the influence of students’ perceptions about the method of teaching teachers to learning outcomes, (3) the influence of learning independence and students’ perceptions of teacher teaching methods on student outcomes. This rtype of research is descriptive quantitative research. The population of this study was class students X accounting and financial institutions and online marketing businesses in SMK Negeri 1 Padang Panjang consisting of 125 students, the sample of this study was 96 students. Data is collected by documentation and questionnaire. The questionnaire method was used to collect data on learning independence variables and student perceptions od teacher teaching methods that had been tested for validity and reliability, while the documentation method was used to collect variable data on general administration learning outcomes. The analysis prerequisite test included normality test, heteroscedasticity tes and mulitcollinearity test. Hypothesis testing is done using multiple analysis regression analysis. The results of this study are: (1) there is a positive and significant influence of elarning independence on learning outcomes, (2) there is a positive and significant influence of student perceptions od teacher teaching methods on learning outcomes, (3) there is a positive and significant influence on learning independence and student perceptions of teaching methods teacher on learning outcomes. Based on the result of the study, obtained 23% of the influence of learning independence and students’ perceptions of the teacher’s teaching methods on students learning outcomes Keyword: learninig independence, students’ perceptions of teacher teaching methods, learning outcomes